Pengembangan Kemampuan Kognitif Anak Dengan Menggunakan Media Papan Pintar Angka - Mezi Rahmayanti; Desri Wahyuni; Desi Anggraini (LPPI Yayasan Almahmudi bin Dahlan, 2023)
This background of this research is the low ability of children to understand concept of numbers, one of the alternatives offered by researchers is the introduction of understand of numbers by . The research method used was classroom action research conducted in 2 cycles. Data collection methods used are observation, assignment and documentation. The results showed that the children's cognitive abilities in recognizing number symbols which developed very well in each indicator showed a good increase after the action was carried out in cycle II, where children could recognize number symbols 1-10 with a percentage of 90%, children could show number symbols 1-10 in sequence with a percentage of 90%, children paired symbol numbers 1-10 with picture media with a percentage of 90%, and children could name symbols of numbers 1-10 in sequence with a percentage of 90%. Keywords: Cognitive Abilities, Smartboard number, Demonstration Learning Method